THE PRESS IN THE FRENCH REVOLUTION (Authors: J. Gilchrist &. W. J. Murray) - Maconochie, A. K. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1973)
J. Gilchrist &. W. J. Murray. THE PRESS IN THE FRENCH REVOLUTION. Melbourne: Cheshire, 1971. 334 pp. $8.50.